Department of Microbiology, Institute of Medical Sciences, Banaras Hindu University, Varanasi-221005, Uttar Pradesh, India - Sheetal Ramachandran; Darsan Balakrishnan Menon (International Journal of Phytomedicine, 2016)
Lactic acid fermentation and not oxidative phosphorylation is reported to be one of the major bioenergetics mechanisms by which cancer cells thrive and proliferate with such rapidity in non-ambient hypoxic conditions. The objective of the study was to determine the synergistic effect of spices in a decoction; Turmeric (Curcuma longa), Pepper (Piper nigrum) and Garlic (Allium sativum) in combination, on the metabolism of Hep G2 liver cancer cells.The biochemical studies of 2 major enzymes involved in cellular metabolism of cells namely; Pyruvate dehydrogenase (PDH) and Lactate dehydrogenase A (LDHA) showed that the decoction down regulated the activity of LDHA and increased the activity of PDH in cancer cells, thereby shifting the metabolic mechanism towards normal functioning in the cancer cells. The expression studies of major molecules involved in regulating metabolic machinery in cells viz., tumour suppressor p53 and oncogene MYC mRNAs; and western blot analysis of Hypoxia inducible factor-1-alpha (HIF-1α) and Vascular endothelial growth factor (VEGF) showed that the decoction regulated the expression of these factors helping to revert the metabolism in cancer cells, which could be attributed to the effect of turmeric and also garlic, rich in pantothenic acid, that aids in turning on oxidative phosphorylation in cancer cells. With the above results, it could be concluded that the decoction alters the metabolic mechanism in a cancer cell from lactic acid fermentation to oxidative phosphorylation, like in any other normal cell, thus inhibiting further growth of the cancer.